2011
DOI: 10.1111/j.1542-4758.2011.00531.x
|View full text |Cite
|
Sign up to set email alerts
|

Tinzaparin reduces health care resource use for anticoagulation in hemodialysis

Abstract: Anticoagulation is required during hemodialysis to prevent thrombus formation within the extracorporeal circuit. The low-molecular-weight heparin tinzaparin is more expensive than unfractionated heparin (UFH) in Canada but more convenient to administer. We conducted a time-and-motion study to test the hypothesis that tinzaparin may reduce nursing time and total health care costs compared with UFH. Data on health care resource use associated with anticoagulation during hemodialysis for chronic renal failure wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…The costs of LMWHs vary not only from country to country, but can also vary from hospital to hospital within the same country, but over time the cost differential between LMHWs and UFH is falling. Despite potentially a higher cost, many studies have reported similar overall treatment costs when taking into account the ease of administration of a prefilled syringe compared to the costs and nursing time spent in setting up a UFH infusion . Although there is no simple bed side test of anticoagulation, due to the greater reliability of drug dosages compared to UFH, most centers simply adjust the dose according to clinical assessment of the extracorporeal circuit and time for the needle sites to stop bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The costs of LMWHs vary not only from country to country, but can also vary from hospital to hospital within the same country, but over time the cost differential between LMHWs and UFH is falling. Despite potentially a higher cost, many studies have reported similar overall treatment costs when taking into account the ease of administration of a prefilled syringe compared to the costs and nursing time spent in setting up a UFH infusion . Although there is no simple bed side test of anticoagulation, due to the greater reliability of drug dosages compared to UFH, most centers simply adjust the dose according to clinical assessment of the extracorporeal circuit and time for the needle sites to stop bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Studies which have compared with LMWHs with UFH, have reported shorter needle site bleeding times post dialysis, with either similar or less circuit clotting and bleeding episodes than UFH, and improved urea clearances due to reduced dialyzer membrane fouling and fewer cases of heparin induced thrombocytopenia …”
Section: Clinical Use Of Lmwhsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of heparin as a locking solution has been the standard of care in this era due to its efficacy, reasonable side effect profile, and cost-effectiveness. [24,25] In studies that used large central venous catheters for dialysis, heparin was shown to be superior to normal saline when used as a flush in dialysis catheters, keeping them more patent, decreasing the need of rt-PA to lyse formed clots within catheters, and improving catheter survival. [25][26][27][28][29] Conversely, some other studies showed that heparin flushed not to be different from normal saline; not to increase the duration of catheter use or to improve its functionality and may prolong aPTT significantly; [29,30] worth noting that these studies used smaller catheters either in peripheral intravenous catheters in children or as arterial catheters.…”
Section: Discussionmentioning
confidence: 99%
“…Annual costs included drug price, medical supplies and nursing time and were extrapolated for the six-month study and nursing time evaluation. Cost for nursing time were calculated by multiplying nursing time by average hourly wage for nephrology nurses in Quebec, including social benefits, obtained from the Quebec Ministry of Health [17]. …”
Section: Methodsmentioning
confidence: 99%